A MUSICALIZAÇÃO ATRAVÉS DE JOGOS MUSICAIS: REFLEXÕES E PROPOSTAS DE ATIVIDADES PARA O ENSINO FUNDAMENTAL I - ARTHUR HENRIQUE SOUSA DE OLIVEIRA (2024)
This study investigates musical education through playful activities, highlighting play as a universal language and an essential pedagogical tool for children's holistic development. Based on playfulness and the exploration of body movement, the research seeks to promote musical learning in a creative and inclusive manner, aligning educational practices with the guidelines of the Brazilian National Common Curricular Base (BNCC). Elements such as auditory perception, motor coordination, socialization, expressiveness, creativity, and improvisation are explored as central to students' engagement and learning. The proposals are designed for application in elementary schools, considering the sociocultural particularities of Campo Grande, MS. Moreover, the study reflects on the importance of stimulating children’s imagination and capacity for improvisation, fostering creative autonomy and awareness of various musical elements. This approach not only broadens students' cultural repertoire but also enhances their social integration, valuing artistic expression and inclusion within the educational process. The research emphasizes the teacher's role as a mediator, encouraging active student participation in musical learning and promoting a more humanized and meaningful education. KEYWORDS: Music education; Playfulness; Music games